2000
DOI: 10.1212/wnl.55.3.388
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in ALS depends on factors other than strength and physical function

Abstract: QOL, as assessed by the patient with ALS, does not correlate with measures of strength and physical function, but appears to depend on psychological and existential factors, and thus may be measured well by the MQOL scale. Spiritual factors and support systems appear to play roles as well. SIP/ALS-19 is a good measure of physical function, but not of overall QOL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
157
2
6

Year Published

2001
2001
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(185 citation statements)
references
References 26 publications
20
157
2
6
Order By: Relevance
“…However, the role of religiosity/spirituality in decision-making was not specifically asked about and this could be seen as a limitation: religiosity (found elsewhere to maintain quality of life in pwALS [44]) may be something that is only discussed once prompted. In our related quantitative study where pwALS were specifically asked about religiosity, lower levels of religiosity were more likely to be associated with intervention refusal [17].…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of religiosity/spirituality in decision-making was not specifically asked about and this could be seen as a limitation: religiosity (found elsewhere to maintain quality of life in pwALS [44]) may be something that is only discussed once prompted. In our related quantitative study where pwALS were specifically asked about religiosity, lower levels of religiosity were more likely to be associated with intervention refusal [17].…”
Section: Discussionmentioning
confidence: 99%
“…At home, particular attention is placed to family dynamics; the intervention here is characterized by the creation of a proper setting. In Help Groups the psychologist focuses on the resources of each participant; coping strategies [29] are shared among the participants to face distress and to create a networking against existential isolation [18][19][20][21][22][23][24][25][26][27][28][29][30]. During the last decade, attention to psychological approach in neuromuscular diseases increased [31], nevertheless a definite model of intervention is absent and there is a lack of guidelines in literature.…”
Section: Discussionmentioning
confidence: 99%
“…Psychological intervention during the progression of the disease consists in one or more psychoeducational sessions, psychological support and mediation. The aim is to restrain the distress and to reinforce the resources of the context [17][18][19][20][21].…”
Section: It Is Recommended To Plan Periodical Meetings With the Care mentioning
confidence: 99%
“…Multiple studies in several populations have shown that nonmotor symptoms over time are among the most function-limiting for patients, and affect caregiver burden and overall quality of life more than motor symptoms. [54][55][56] The management of these debilitating symptoms depends on their recognition by physicians. 57 Research suggests that as many as 50% of patients with PD who have depression are not treated, despite evidence that treatment parallels that of the general population (e.g., selective serotonin reuptake inhibitors for depression and anxiety).…”
Section: Symptom Assessment and Managementmentioning
confidence: 99%